HUBUNGAN SIKAP SISWA TERHADAP PENGAJARAN SEJARAH DENGAN HASIL BELAJAR DALAM MATA PELAJARAN SEJARAH DI SMA NEGERI 1 BATANG ANAI - Andriani, Reski - (Pendidikan Sejarah, 2014)
In learning historical the students just repeating the same things from elementary school until university level. Students attitudes about the teaching of history in the subject of History and the reaction of their seriousness for this subjects. Students have a positive attitude in history subjects if they know function of this subject. This research aims to describe and analyze, (1) students attitudes toward the teaching of history, class XI IPS SMA Negeri 1 Batang Anai, (2) the relationship of students attitudes toward teaching history to students learning outcomes SMA Negeri 1 Batang Anai in Semester academic year 2013/2014. Kind of research is ekspasfacto uses a quantitative approach to research site in SMA Negeri 1 Batang Anai.Samplingwere students of class XI IPS SMA Negeri 1 Batang Anai enrolled in the academic year 2013/2014 with 49 people. The data got through a questionnaire statement. Based on the results, research data with respect to the calculation of the level of achievement the respondents can be seen that for a confidence score of 67 was entered into the fair category, level of achievement with respect to feeling respondents obtained a score of 71 and entered into the fair category, to the level of achievement of the respondents with respect to the tendency obtained a score of 69 and entered into fair category, then overall attitude variable TCR (achievement Level Respondents) attitude score was 68.78 and put in a category less. The continiue with the testing of the relationship between students attitudes (X) on learning outcomes (Y) is the contribution parsentase students attitudes toward student learning outcomes by 24%. From the analysis of simple correlation (r) obtained correlation relationship students attitudes toward learning outcomes (r) is 0.485 whereas count (r) 0,281 tables. Based on this research hypothesis is zero (H0) is rejected it means there is a relationship between students attitudes to learning outcomes.